Creative city practices in the Lusophone space - Murányi, Kata (2017)
The purpose of this paper is to discuss the creative city, and thus urban creativity in the Portuguese-speaking world, through eight in-depth interviews with leading figures of creative city practices in São Paulo and Lisbon. Both cities share a common language, similarities in history and culture, and in recent years they have been facing serious economic, political and social problems. Over the last few decades, various initiatives have been created with aims of involving and collaborating with locals in order to directly influence the quality of urban life. This research explores how changes in power and political and economic circumstances influence both the city and the lives of locals. I examine how specific bottom-up initiatives address various problems in society; I assess the best practices of urban creativity and how current problems and solutions arise in a contemporary metropolis. The research is based on study trips to São Paulo and Lisbon in 2016 where a number of interviews were conducted with representatives active in innovative creative economy organizations, routinely providing solutions to the needs of people in urban public spaces.